Volume 8: Seismic Engineering 2014
DOI: 10.1115/pvp2014-29012
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Evaluation Method for Seismic Isolation Systems of Nuclear Power Facilities: Part 3 — Seismic Response of Crossover Piping for Seismic Isolation System

Abstract: This paper, which is part of the series entitled “Development of an Evaluation Method for Seismic Isolation Systems of Nuclear Power Facilities”, shows the linear seismic response of crossover piping installed in a seismically isolated plant. The crossover piping, supported by both isolated and non-isolated buildings, deforms with large relative displacement between the two buildings and the seismic response of the crossover piping is caused by two different seismic excitations from the buildings. A flexible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With regard to the failure mode of the crossover piping, some studies were conducted to apply seismic isolation systems to LWRs as a part of a national Japanese project (Otani et al, 2014;Otoyo et al, 2014). These studies concluded that the failure mode of the crossover piping under seismic loads was low-cycle fatigue, similar to that of the piping of ordinary non-isolated plants, through a series of dynamic tests using a 1/10 scale model and analyses.…”
Section: Overview Of the Design Codesmentioning
confidence: 99%
“…With regard to the failure mode of the crossover piping, some studies were conducted to apply seismic isolation systems to LWRs as a part of a national Japanese project (Otani et al, 2014;Otoyo et al, 2014). These studies concluded that the failure mode of the crossover piping under seismic loads was low-cycle fatigue, similar to that of the piping of ordinary non-isolated plants, through a series of dynamic tests using a 1/10 scale model and analyses.…”
Section: Overview Of the Design Codesmentioning
confidence: 99%